Cardiac autonomic dysfunction is associated with hypothalamic damage in patients with childhood-onset craniopharyngioma. - Hae Woon Jung (PLoS ONE, 2021)
Background Autonomic nervous system dysfunction is implicated in the development of hypothalamic obesity. We investigated the relationship between hypothalamic involvement (HI), central obesity, and cardiac autonomic dysfunction by assessing heart rate variability (HRV) indices in patients with childhood-onset craniopharyngioma. Methods A cross-sectional study of 48 patients (28 males, 10-30 years old) with hypothalamic damage after childhood-onset craniopharyngioma was performed. Postoperative HI was graded as mild (n = 19) or extensive (n = 29) on magnetic resonance imaging. Anthropometry, body composition and HRV indices including the standard deviation of all normal R-R intervals (SDNN) and total power (TP) as overall variability markers, root-mean square differences of successive R-R intervals (RMSSD) and high frequency (HF) as parasympathetic modulation markers, and low frequency (LF) as a sympathetic/sympathovagal modulation marker were measured. Results Patients with extensive HI had increased means of body mass index, waist circumference, and fat mass than those with mild HI (P < 0.05, for all). Centrally obese patients had a lower mean HF, a parasympathetic modulation marker, than centrally non-obese patients (P < 0.05). The extensive HI group had lower means of overall variability (SDNN and TP), parasympathetic modulation (HF), and sympathetic/sympathovagal modulation (LF) than the mild HI group (P < 0.05, for all). The interaction effect of HI and central obesity on HRV indices was not significant. In models adjusted for age, sex, and family history of cardiometabolic disease, the means of the overall variability indices (P < 0.05 for both SDNN and TP) and a sympathetic/sympathovagal modulation index (P < 0.05 for LF) were lower with extensive HI, without differences according to central obesity. Conclusions The reduced HRV indices with extensive HI suggests that hypothalamic damage may contribute to cardiac autonomic dysfunction, underscoring the importance of minimizing hypothalamic damage in patients with childhood-onset craniopharyngioma.